2022
DOI: 10.3390/ijms23042383
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Copper-Based Solid Heterogeneous Catalysts for Azide–Alkyne Cycloaddition Reactions

Abstract: The copper(I)-catalyzed azide−alkyne cycloaddition (CuAAC) reaction is considered to be the most representative ligation process within the context of the “click chemistry” concept. This CuAAC reaction, which yields compounds containing a 1,2,3-triazole core, has become relevant in the construction of biologically complex systems, bioconjugation strategies, and supramolecular and material sciences. Although many CuAAC reactions are performed under homogenous conditions, heterogenous copper-based catalytic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 160 publications
0
21
0
Order By: Relevance
“…Furthermore, metals like Ru, Ag, Au, Ir, Ni, Zn, and Ln have also been used to catalyze azide-alkyne cycloaddition reactions for the regioselective synthesis of 1,4or 1,5-disubstituted or 1,4,5-trisubstituted triazoles (Scheme 1a), which depend on reagents (e.g., aliphatic or aromatic) and the selected conditions for a CuAAC reaction, as summarized in Scheme 1b. 47 Fokin et al 48 reported direct evidence for a binuclear Cu intermediate's involvement and a number of stages involving Cu (I) -aryl intermediates have been proposed in Scheme 2a and b. During this mechanism, two Cu atoms are required to formation of the active cycloaddition complex and their relation was described.…”
Section: Reaction Chemistry and Engineering Perspectivementioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, metals like Ru, Ag, Au, Ir, Ni, Zn, and Ln have also been used to catalyze azide-alkyne cycloaddition reactions for the regioselective synthesis of 1,4or 1,5-disubstituted or 1,4,5-trisubstituted triazoles (Scheme 1a), which depend on reagents (e.g., aliphatic or aromatic) and the selected conditions for a CuAAC reaction, as summarized in Scheme 1b. 47 Fokin et al 48 reported direct evidence for a binuclear Cu intermediate's involvement and a number of stages involving Cu (I) -aryl intermediates have been proposed in Scheme 2a and b. During this mechanism, two Cu atoms are required to formation of the active cycloaddition complex and their relation was described.…”
Section: Reaction Chemistry and Engineering Perspectivementioning
confidence: 98%
“…, aliphatic or aromatic) and the selected conditions for a CuAAC reaction, as summarized in Scheme 1b. 47…”
Section: Cuaac Click Reactionsmentioning
confidence: 99%
“…1,3‐Dipolar cycloaddition reaction of organic azides and alkynes has gained considerable attentions [11a–k] . 1,2,3‐Triazole scaffolds are major products.…”
Section: Synthesis Of Triazolesmentioning
confidence: 99%
“…This was publicly recognized with the award of Nobel Prize in Chemistry to Morten Meldal, Carolyn R. Bertozzi and K. Barry Sharpless in 2022. [5][6][7][8] Researchers in this area have focused on developing more sustainable conditions by seeking greener solvents and copper precursors that can generate copper(I) efficiently, while decreasing or eliminating the need for reducing agents and bases.…”
Section: Introductionmentioning
confidence: 99%